Effect of non-thermal plasma on cellulose crystallinity and lignin content in corn stalks - Grbić, Jovana; Đukić-Vuković, Aleksandra; Mladenović, Dragana; Lazović, Saša; Mojović, Ljiljana (Journal on Processing and Energy in Agriculture, 2022)
Lignocellulosic biomass is a cheap raw material that can be used in fermentation for the production of biofuels, biogas and other compounds thanks to its high carbohydrate content. The complex structure, including cellulose, hemicellulose and lignin, requires prior biomass treatment to facilitate hydrolysis to simple sugars. Today, biomass is only partially exploited and generates about 14% of the world´´ s energy. This is because the most commonly used physical, chemical and physicochemical treatments are not sustainable. They are energy-consuming but still low in productivity and toxic inhibitors formed during these treatments could hinder later steps of fermentation. Treatment of biomass with advanced oxidation techniques has great potential as environmentally friendly, the so-called "green" treatment. During these processes, reactive species (radicals, electrons, ions and peroxides) are formed and they attack cellulose, hemicellulose and lignin components. In this paper, the effects of non-thermal plasma, Fenton process and combined non-thermal plasma/Fenton treatments of corn stalks were compared. Grounded biomass of corn stalks was mixed with Fenton reagent and hydrogen peroxide in different ratios and subjected to non-thermal plasma treatment. Carbohydrate content was decreased in the samples treated by non-thermal plasma both with and without Fe2+. However, specific biomass:Fe2+:H2O2 ratio was needed to achieve the highest rate of lignocellulose decomposition. Cellulose and hemicellulose fractions were affected and reduced by the studied treatments but resulted in almost no changes in cellulose crystallinity index. The lower lignin content and cellulose crystallinity enable more efficient enzyme hydrolysis of treated lignocellulose and novel options for valorization in fermentations.